The The Influence of Transformational Leadership and Employee Integrity through Organizational Citizenship Behavior (OCB) on Employee Innovation in Regency / City Inspectorates - Praseno Hadi; Hamidah; David Paul Saerang (Journal of Business and Behavioural Entrepreneurship, 2020)
This study aims to analyze and discuss the effect of Transformational Leadership and Employee Integrity through Organizational Citizenship Behavior (OCB) Against Employee Innovation at Regency / City Inspectorates in North Sulawesi Province. This research is a quantitative study, using a survey method with a causal approach, with data analysis techniques using Structural equation modeling (SEM) analysis. Research respondents numbered 200 employees at the District / City Inspectorate in North Sulawesi Province. The results of this study indicate that 1) Transformational leadership has a direct and positive effect on employee innovation. The better the leadership at the regional Inspectorate adopts the transfrormational leadership style, the better the innovator will be at the regional inspectorate. 2) Integrity has a direct and positive effect on employee innovation. The more integrity with APIP Regional Inspectorate, the better will be innovations in the field of supervision. 3) Organizational citizenship behavior (OCB) has a direct and positive effect on employee innovation. The better the Organizational Citizenship Behavior (OCB) of the APIP Regional Inspectorates, the innovations of the APIP in the field of supervision will also increase. 4) Transformational leadership has a direct and positive effect on organizational citizenship behavior (OCB). The better the leadership at the regional Inspectorate adopts the transformational leadership style, the more it increases organizational citizenship behavior (OCB) from the APIP. 5) Employee integrity has a direct and positive effect on organizational citizenship behavior (OCB). The more integrated the APIP regional Inspectorate, the better the organizational citizenship behavior (OCB) of the APIP. 6) Transformational leadership has an indirect and positive effect on employee innovation through organizational citizenship behavior (OCB). 7) Employee integrity has an indirect and positive effect on employee innovation through organizational citizenship behavior (OCB).